Silence in the second language classroom - King, James Edward (2011)
This mixed-methods investigation reports on the under-researched issue of silence within Japanese university second language (L2) classrooms. An extensive, multi-site study using a structured observation methodology was employed to investigate the classroom behaviour of over 900 language learners across nine universities in Japan. To effectively measure the extent of macro-level silence within their classrooms, an original observation instrument called the Classroom Oral Participation Scheme (COPS) was specially developed for the task. A total of 48 hours of data was collected using a minute-by-minute sampling strategy which resulted in some startling results. Learners were found to be responsible for less than one percent of initiated talk within their classes, while over a fifth of total class time observed was characterised by no oral participation by any participants. Complementing the COPS' quantitative evidence of a robust national trend of silence in Japan's universities, a parallel qualitative phase of the investigation gave students a voice about their silences by drawing on over seventy-thousand words of transcribed data collected during a series of semi-structured interviews. This phase of the research provided a valuable individual-level analysis of learners' fundamental beliefs about and personal experiences of not speaking in L2 educational contexts. The final phase of the project adopted an event-specific focus on classroom silence by utilising a stimulated recall methodology to uncover what students were actually thinking and feeling whilst silent episodes were in progress during lessons. Using Dynamic Systems Theory (DST) as its conceptual background, the investigation moves away from reductionist, single-cause explanations for learner reticence to suggest that silence actually emerges through multiple, concurrent routes. These routes (termed attractors in DST) are so abundant, and appear to be so well supported both educationally and culturally in the Japanese context, that silence has fossilised into a semi-permanent attractor state within university language classrooms.